(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Purpose: This study empirically investigates the key determinants influencing the adoption and development of sustainable tourism services — specifically eco-tourism and agro-tourism — in Uzbekistan. Methodology: A conceptual model grounded in the Theory of Planned Behavior (TPB) was tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). A structured questionnaire survey was conducted with 347 respondents drawn from Samarkand, Bukhara, and Fergana regions. Findings: Government policy support (β=0.41), environmental awareness (β=0.33), and local community participation (β=0.22) were identified as the strongest predictors of sustainable tourism adoption intention. The model explained 58% of the variance. Contribution: This research addresses the scarcity of empirical data on sustainable tourism in Central Asia and demonstrates the necessity of adapting TPB to the economic context of Uzbekistan.1